2013
DOI: 10.1002/cem.2535
|View full text |Cite
|
Sign up to set email alerts
|

Process analytical chemistry and chemometrics, Bruce Kowalski's legacy at The Dow Chemical Company

Abstract: With the passing of Bruce R. Kowalski in 2012, a true visionary for chemometrics and process analytical chemistry has been lost. Bruce made significant contributions in the area of chemometrics and process analytical chemistry when he was a professor of chemistry at the University of Washington. He developed new and innovative chemometrics technology and founded the Center for Process Analytical Chemistry. He inspired many students and visiting scholars and had a significant impact on the practice of industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 109 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…The results showed that spectral preprocessing should be performed based on an understanding of the physics and chemistry of the material. 59,60…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that spectral preprocessing should be performed based on an understanding of the physics and chemistry of the material. 59,60…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that spectral preprocessing should be performed based on an understanding of the physics and chemistry of the material. 59,60 The right side of Table 4 shows the results of models performed from 1 to 30 film layers as calibration set and with a prediction set that varied from 31 to 50 film layers. The authors anticipated that the larger number of films in the validation set would increase the error.…”
Section: Prediction Of Number Of Filmsmentioning
confidence: 99%
“…The online NIR oxide concentration is shown in green. After an initial increase in unreacted oxide concentration due to a low temperature (red line), the unreacted oxide level is maintained at a constant level as the reactor level increases (black line) and the reactor pressure The implementation of an online FTNIR instrumentation and models at Dow [26] enabled reduction in offgrade by providing real-time data to operations, as well as the ability to manage the quality assurance of product storage tanks using a statistical approach, which in some cases eliminates the need for interim storage. Additional cost savings is achieved through significant reduction in reactor sampling and associated lab testing, which is compounded by the multiple tests performed on each reactor sample.…”
Section: Polyol/polyglycolmentioning
confidence: 99%
“…The implementation of an online FTNIR instrumentation and models at Dow enabled reduction in off‐grade by providing real‐time data to operations, as well as the ability to manage the quality assurance of product storage tanks using a statistical approach, which in some cases eliminates the need for interim storage. Additional cost savings is achieved through significant reduction in reactor sampling and associated lab testing, which is compounded by the multiple tests performed on each reactor sample.…”
Section: Polyol/polyglycolmentioning
confidence: 99%
“…Another approach is to consider all the data together and use multivariate statistical process control (MSPC) (also known as chemometrics) for process monitoring. While this is well‐regarded technology, [ 4,5 ] one of the challenges has been how to deploy MSPC methods to those not trained in chemometrics. This paper discusses how to deploy both EMI and MSPC to those not trained in multivariate methods or data science.…”
Section: Introductionmentioning
confidence: 99%